IN VITRO IN VIVO CORRELATION OF DEXTROMETHORPHAN HYDROBROMIDE MODIFIED RELEASE TABLETS: AN INTERNAL VALIDATION EVALUATION - N, Ramesh; Colaco, Socorrina; Shabaraya, Ramakrishna; Rajan, Sekar; Nainar Meyyanathan, Subramania (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objectives: The purpose of this study was to develop and validate in vitro and in vivo correlation (IVIVC) for newly developed dextromethorphan hydrobromide sustained-release (SR). Methods: During the development of a once-daily SR tablet of dextromethorphan hydrobromide, an extrapolative in vitro drug release method was designed and statistically evaluated using three formulations with varying release rates. The similarity factor (f2) was used to analyze the dissolution data. Three-way crossover study design was conducted in six healthy human subjects under fasting condition. Result: The formulations were evaluated by using area under the plasma concentration-time curve, (AUC0-∞), time to reach peak plasma concentration, Tmax, and peak plasma concentration Cmax, while correlation was determined between in-vitro release and in-vivo absorption. A linear correlation was observed between the absorption and dissolution profiles of the drug. The prediction error (%) was determined to check how well a given model can accurately predict a pharmacokinetic parameter of the drug. The predicted Cmax and AUC found to be −6.98 and −8.55 and for AUC was 7.76 and 8.82% respectively. Conclusion: In conclusion, a Level A IVIVC explaining the complete time-course of plasma concentrations was developed and validated, internally for developed dextromethorphan hydrobromide SR formulations. Keywords: Dextromethorphan hydrobromide, Dissolution, Bioavailability, Sustained-release, In vitro and in vivo correlation.